Over the awareness of managers strategic importance of vigilance: "Exploratory study in the National Insurance Company" (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The rapid reality of events in the information era, and the enormous pressure of forces market, competition, permanent movement of the markets and consumers and the large development unprecedented of technology in all areas make a lot of organizations find it difficult to keep up with this rapid developments .Here was the role of strategic vigilance closer organization to their environment ,and play an active role in providing the necessary information to make decisions and insurance companies are not far from those changes .On this basis the researcher offered studied(Over the awareness of managers of insurance companies for strategic vigilance).Choosing sample of 35 managers in the National Insurance Company to test the hypothesis of the study, which states (there is awareness by managers in the National Insurance Company for strategic vigilance).The study found that there are in the National Insurance Company vigilance and awareness by managers, but they need to larger development  and more interesting.